A label-free fluorescent aptasensor based on the AIE effect and CoOOH for ultrasensitive determination of carcinoembryonic antigen. Issue 44 (7th November 2022) - Ju, Yulong; Tang, Qiukai; Yang, Yiwen; Zeng, Yanbo; Zhai, Yunyun; Wang, Hailong; Li, Zuguang; Li, Lei
Abstract : A label-free fluorescent aptasensor based on the AIE effect and CoOOH platform was developed and used to detect CEA with high sensitivity and specificity. The proposed aptasensor can detect CEA in serum samples of cancer patients with high accuracy. Abstract : Highly sensitive and specific detection of cancer markers (such as carcinoembryonic antigen) is very important for early diagnosis and treatment of cancer. Herein, we developed a label-free fluorescent aptamer biosensor based on the aggregation-induced emission (AIE) effect and hydroxycobalt oxide (CoOOH) platform, and used it to detect carcinoembryonic antigen (CEA) with high sensitivity and specificity. Fluorescent ionic liquid Compound B can combine with a CEA aptamer (CEA-Apt) through electrostatic attraction and hydrophobic interaction to form an ionic liquid/aptamer (CEA-Apt/B) complex and produce the AIE effect, thereby enhancing the fluorescence intensity of B. CEA-Apt/B was adsorbed on the surface of CoOOH when CoOOH was added to the buffer solution, and the fluorescence of B was quenched. After adding CEA to the solution, CEA-Apt/B bound to CEA and separated from the surface of CoOOH because CEA-Apt had stronger affinity for CEA, resulting in fluorescence recovery of B. In the level range of 0.67–10000 pg mL −1, the fluorescence recovery intensity of the sensor had an excellent linear relationship with the level of CEA, and its LOD was 0.2 pg mL −1 (S/N = 3). In addition, the sensor had good selectivity and can be directly used to detect CEA in human serum with high accuracy.